2018
DOI: 10.1016/j.physa.2018.08.133
|View full text |Cite
|
Sign up to set email alerts
|

Benford’s law and first letter of words

Abstract: A universal First-Letter Law (FLL) is derived and described. It predicts the percentages of first letters for words in novels. The FLL is akin to Benford's law (BL) of first digits, which predicts the percentages of first digits in a data collection of numbers. Both are universal in the sense that FLL only depends on the numbers of letters in the alphabet, whereas BL only depends on the number of digits in the base of the number system. The existence of these types of universal laws appears counter-intuitive. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…The results of our research indicate that Benford's Law (BL) can be applied for detecting data anomalies compared to the original unaffected dataset. Similar to previous studies [22][23][24][25][26][27][28][29][30][31][32][33][34], our research also confirms that the more data is manipulated, the more accurate the results become. Therefore, using BL for minor data changes is not recommended.…”
Section: Discussionsupporting
confidence: 90%
“…The results of our research indicate that Benford's Law (BL) can be applied for detecting data anomalies compared to the original unaffected dataset. Similar to previous studies [22][23][24][25][26][27][28][29][30][31][32][33][34], our research also confirms that the more data is manipulated, the more accurate the results become. Therefore, using BL for minor data changes is not recommended.…”
Section: Discussionsupporting
confidence: 90%
“…Checking for the validity of BL in this dataset would be the best approach in a forensic analysis looking at potential manipulations of the number of cases [7] , [8] , since a distribution of first digits that deviates from the expected distribution may indicate fraud. Prior studies have shown that BL is also applicable to genome data [9] , the half-lives of unstable nuclei [3] , self-reported toxic emissions data [10] , tax auditing [11] , accounting [12] , election data [13] , [14] , stock markets and final data [15] , [16] , [17] , [18] , [19] , [20] , regression coefficients [21] , inflation data [7] , World Wide Web [22] , religions [23] , [24] , [25] , birth data [26] , river data [27] , first letter words [28] , elementary particle decay rates ( [29] , astrophysical measurements [30] , and more.…”
Section: Introductionmentioning
confidence: 99%
“…Jordan et al (2004) identify numerous studies that mobilize BL and demonstrate that this law represents a viable method for detecting manipulations of data. Moreover, there are attempts to use Benford's law in the analysis of data different than digits/numbers: Yan et al (2018) propose a first-letter law that predicts the percentages of first letter for words in novels.…”
Section: Introductionmentioning
confidence: 99%